Advancing Cybersecurity Use of Sensitive Data in Electronic Healthcare System: A Review of Privacy and Regulations - Ugochukwu, Okwudili Matthew; Rosa, Renata Lopez; Adenike, Oyedemi Oluyemisi; Rodriguez, Demostenes Z. (INFOCOMP Journal of Computer Science, 2025)
Addressing cybersecurity challenges in electronic health system is imperative in ensuring trustworthiness of distributed healthcare information systems, thereby safeguarding sensitive patient information and optimizing healthcare service delivery. The use of data-driven technologies presents a promising opportunity for significant advances in information management required for an improved healthcare privacy protection for patients care, offering opportunities toward increased database accessibility in healthcare information system. This not only guarantees adherence to legal frameworks but also lays the groundwork for the ethical and accountable application of distributed systems in the medical field. To gain a thorough grasp of the requirements for cybersecurity in healthcare workforce groups, this paper applied a methodology that relied on a survey questionnaire. After that, it uses a risk-based methodology to estimate the risk of different cybersecurity and data privacy threats related to the stakeholder, determines the best ways to mitigate those cybersecurity risks, and suggests subsets of human-centric policies to manage each cybersecurity risk in the distributed healthcare setting. The results we obtained indicate that the effective management of individual cybersecurity risks across various healthcare organizations and diverse employee groups are facilitated by the adoption of a risk-based strategy for information privacy and cybersecurity risks protection.